1981
DOI: 10.1111/j.2042-7158.1981.tb13851.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine release from the myenteric plexus of guinea-pig ileum by prostaglandin E1

Abstract: Release of acetylcholine (ACh) by prostaglandin E1 from the nerve terminals of the guinea‐pig longitudinal muscle strip was studied in order to reveal the effect of PGE1 on myenteric plexus activity. The ACh released was collected in the presence of physostigmine (2·1 μg ml−1) and choline (0·1 μg ml−1) at 38° C. Five to 100 ng ml−1 PGE1 enhanced the release dose‐dependently. The effect was maintained during the presence of PGE1 in the organ bath, while rapid tachyphylaxis was observed with the ACh‐releasing ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Our results are consistent with previous observations that transmural stimulation response is due predominantly to ACh released from parasympathetic nerve endings (Paton & Zar, 1968). (1 Yagasaki et al (1981) have also shown that PGE1 increases resting ACh release from guinea-pig isolated ileum. Enhancement of the contractile power of the transmitter at the postsynaptic membrane cannot be ruled out as an additional factor in the action of PGE2.…”
Section: Discussionsupporting
confidence: 83%
“…Our results are consistent with previous observations that transmural stimulation response is due predominantly to ACh released from parasympathetic nerve endings (Paton & Zar, 1968). (1 Yagasaki et al (1981) have also shown that PGE1 increases resting ACh release from guinea-pig isolated ileum. Enhancement of the contractile power of the transmitter at the postsynaptic membrane cannot be ruled out as an additional factor in the action of PGE2.…”
Section: Discussionsupporting
confidence: 83%
“…PGE also reversed IND-induced inhibition of ACh release (Yagasaki et al, 1981;1984). Thus, the ACh release from myenteric plexus may be modulated by various kinds of endogenous PGs.…”
Section: Discussionmentioning
confidence: 86%
“…The longitudinal muscle of the ileum with the myenteric plexus attached was removed as pre viously described (20). The preparation was mounted in an organ bath containing 3 ml of Tyrode's solution of the following composition: 136.9 mM NaCl, 2.7 mM KC1, 1.8 mM CaC12, 1.05 mM MgC12, 11.9 MM NaHCO3, 0.4 mM NaH2PO4 and 5.6 mM glucose.…”
Section: Methodsmentioning
confidence: 99%